Enhancing the impact and sustainability of development strategies with smallholder farmers: participatory engagement, whole farm modelling and farmer-led on-farm research. Issue 6 (2nd November 2019) - McDonald, Cam; Corfield, Jeff; MacLeod, Neil; Lisson, Shaun
ABSTRACT: Thousands of agricultural research for development projects around the world aimed at assisting smallholder farm households secure a better livelihood have not achieved sustained integration of new technologies into local farming systems or beyond the immediate communities in which they were sited. This paper describes an integrated systems approach, which has been applied successfully in several countries, incorporating: (1) benchmarking (or defining) a current system; (2) application of whole-farm systems modelling of potential intervention strategies; (3) on-ground testing by smallholders, and adaptation where necessary, and; (4) assuming success, using these participant smallholders to transfer the knowledge to other smallholders, both locally and regionally, and integrate the technology into the local farming systems in a sustainable manner.